Gnezditvena biologija rakarja Acrocephalus arundinaceus na ribnikih v Dragi pri Igu na Ljubljanskem barju (Slovenija) - Božič, Ivo A. (Acrocephalus, 1999)
During 1981-1999, the breeding biology of the Great Reed Warbler was monitoredat the 16.6 ha large system of discharge fish-ponds at Draga near Ig at Ljubljansko barje. 328 nests were found during the entire period. In the breeding season I visited the fish-ponds 25 times on average per year. The annual breeding success oscillated between 24% and 86%, while in the entire period its average was 56%. The smallest distance between two occupied nests was 3 ni. The majority of the nests were built in common reed Phragmites australis above the water level and only in two cases above solid earthč once it was built in great reedmace Typha sp. and once in rush Juneus sp. The nestswere situated SS cm above the water level on average and supported by 5-6reed stalks. The average depth of the water under the nests was 64 cm. The average height of the nests was 11.8 cm, the average diameter 10.2 cm, and theaverage depth of the nest cup 7 cm. The first eggs were laid on May 3rd, the majority of them on May 15th. The average size of the 1,027 measured eggs was 22.8 x 16.4 mm, their average weight reaching 2.9 g. Most of the nests contained 5 eggs (2-6), or 4.8 on average. Only about 6% of the Great Reed Warbler pairs built the second nest as well. The number of eggs in the 27 second clutch nests was 2-5, or 3.4 on average. The hatched young weighed about 2.3 gč in three days they doubled this figure and after a week reached the weight of their parents. After 10-12 days they left their nests, even before being able to fly. There were normally 4 or 5 (even 6) young in the nests, exceptionally a single chick (3.9 on average). The successfully fledgednests contained 3.7 chicks, or 2Č2 young per all found nests 655 chickswere ringed in their nests. (Abstract truncated at 2000 characters)
Keywords: bird; ptice; ornitologija; Draga pri Igu; rakar; Ljubljana Marshes; Ljubljansko barje; Slovenia; Slovenija; gnezdenje